Police community support officers in England: a dramaturgical analysis - O'Neill, Megan (Policing and society, 2017)
Police community support officers (PCSOs) have become an integral part of neighbourhood policing teams (NPTs) in England and Wales since the national roll-out of neighbourhood policing in 2008. Most research on PCSOs examines their outward-facing role, such as in the extent to which these police staff have become community engagement or enforcement-orientated. While this is important to consider, what is also important is the manner in which PCSOs have been accepted by the police organisation internally. This can have a bearing on the degree to which PCSOs are able to fulfil their roles in neighbourhood policing. The research reported here is based on a six-month observational study of PCSOs in England. Using Goffman's dramaturgical framework and concept of performance teams, this article argues that PCSOs and police constables (PCs) comprise separate performance teams within each NPT group, although the degree of separation between PC and PCSO teams varied from one NPT to another. One element of this relationship which was generally consistent was that police officers and supervisors tended to value more highly PCSO work which was enforcement-orientated. This challenges PCSOs to enhance this side of their performances in spite of their limited statutory powers. Some PCSOs experienced this as a daily pressure to justify their existence to police colleagues, leaving them as disillusioned and unsatisfied staff. This was clearly expressed in the use of space in these police stations in that PCSOs sought out spaces where they could relax in their own exclusive ‘back stage’ areas, away from police colleagues.